Correlations of strength, proprioception, and tactile sensation to return-to-sports readiness among patients with anterior cruciate ligament reconstruction - Ma, Xiaoli; Lu, Lintao; Zhou, Zhipeng; Sun, Wei; Chen, Yan; Dai, Guofeng; Wang, Cheng; Ding, Lijie; Fong, Daniel Tik-Pui; Song, Qipeng (Frontiers in Physiology, 2022)
Objectives: Anterior cruciate ligament reconstruction (ACLR) is the most common surgery for anterior cruciate ligament (ACL) injuries, and the relationships between patients’ return to sports (RTS) readiness and different physical functions are inconclusive among patients with ACLR. This study aimed to investigate the correlations of strength, proprioception, and tactile sensation to the RTS readiness among patients with ACLR. Methods: Forty-two participants who received ACLR for at least 6 months were enrolled in this study. Their strength, proprioception, and tactile sensation were tested, and their RTS readiness was measured with the Knee Santy Athletic Return to Sports (K-STARTS) test, which consists of a psychological scale [Anterior Cruciate Ligament Return to Sports after Injury scale (ACL-RSI)] and seven functional tests. Partial correlations were used to determine their correlations while controlling for covariates (age, height, weight, and postoperative duration), and factor analysis and multivariable linear regressions were used to determine the degrees of correlation. Results: Knee extension strength was moderately correlated with K-STARTS total, ACL-RSI, and functional scores. Knee flexion strength, knee flexion and extension proprioception, and tactile sensation at the fifth metatarsal were moderately correlated with K-STARTS total and functional scores. Strength has higher levels of correlation with functional scores than proprioception. Conclusion: Rehabilitation to promote muscle strength, proprioception and tactile sensation should be performed among patients with ACLR, muscle strength has the highest priority, followed by proprioception, with tactile sensation making the least contribution.